Research on PAPR reduction algorithm based on CWGAN-SLM for multi-wavelet OFDM system - Guang YANG; Zhaoyang WU; Min NIE; Xiaohong YAN; Fan JIANG (Tongxin xuebao)
In order to meet the demand for low peak to average ratio (PAPR) of orthogonal frequency division multiplexing (OFDM) technology in the future 6G satellite-ground integrated system, an algorithm combining selective mapping (SLM) algorithm and multi-wavelet OFDM technology was proposed firstly.However, the PAPR reduction was limited and the computational complexity was high.To solve this problem, a multi-wavelet OFDM PAPR reduction algorithm based on conditional Wasserstein generative adversarial network (CWGAN) and SLM was proposed, which was called CWGAN-SLM algorithm.CWGAN was introduced to generate more time-domain alternative signals to reduce the PAPR in the CWGAN-SLM algorithm.Simulation results indicate that the CWGAN-SLM algorithm greatly reduces the PAPR of the system and the computational complexity, and has a lower bit error rate.Compared with the GAN and WGAN, the CWGAN has the advantages of easy training, strong stability and good PAPR performance.